Flash glucose monitoring in gestational diabetes mellitus: study protocol for a randomised controlled trial - Agata Majewska; Paweł Stanirowski; Mirosław Wielgoś; Dorota Bomba-Opoń (BMJ Open)
Introduction Gestational diabetes mellitus (GDM) is a glucose intolerance occurring in 3%–10% of pregnant women and being a risk factor for multiple maternal and fetal complications. The risk of perinatal complications is proportional to the level of maternal hyperglycaemia. Proper glycaemic control is therefore one of the key elements of GDM therapy. Until recently, determination of blood glucose concentration was performed using glucose meters, which involved multiple fingerpricks. Nowadays, due to the flash glucose monitoring (FGM) availability, it is possible to collect measurements at any time without routine puncturing. The aim of the presented study is to assess the impact of FGM on the efficacy of treatment in population of patients diagnosed with GDM.Methods and analysis This is a prospective, randomised study, that will recruit 100 women at 24–28 weeks of gestation at the 1st Department of Obstetrics and Gynecology, Medical University of Warsaw, Poland. Women diagnosed with GDM, who will meet the inclusion criteria, will be individually randomised to the FGM or self-monitoring of blood glucose groups. Further on, clinical and laboratory results of the mother and their newborns will be collected for analysis during the course of pregnancy. Primary outcome is mean glycaemia result in each group after 1 month analysis and percentage of results in the target glycaemic range. The secondary objectives will be to compare the two groups for maternal and neonatal outcomes in conjunction with long-term glycaemic control using blood glycated haemoglobin and fructosamine serum concentrations.Ethics and dissemination The study is exempt from regional ethics review due to its nature of quality improvement in patient care. The study has been approved by the Bioethics Committee at the Medical University of Warsaw and the patient privacy protection boards governing over the recruitment sites. Results of the study will be presented in peer-reviewed journals and at conferences.Trial registration number NCT04422821.